The Nigerian legislative process : bills, budgetary control & committee system - Esebagbon, Ray. (Abuja : Law-Link Consults, 2005)
This book covers such issues as the powers, duties and responsibilities of the Nigerian legislature, bills and legislative drafting, budgeting with particular emphasis on the legislature- executive roles in the budgetary process as well as committee system in the Nigerian legislative process.
Includes index.
aug 07/06/13, ijb 19/03/2019
Loans
Keywords: Legislation; Budget; Bill drafting